Simultaneous Left Ventricular and Deep Vein Thrombi Caused by Protein C Deficiency. (17th January 2017) - Maki, Harufumi; Nishiyama, Motohiro; Shirakawa, Motoaki
Abstract : Protein C deficiency is a risk of venous thrombosis because of poor fibrinolytic activity. It remains controversial whether protein C deficiency causes arterial thrombosis. A 21-year-old woman was referred with a chief complaint of right leg pain and numbness. Contrast-enhanced computed tomography revealed a low-density mass in the left ventricle (LV), splenic infarction, and peripheral arterial obstructions in her right leg. Thrombosis extending from the renal vein to the inferior vena cava was also detected. Electrocardiography revealed ST depression in leads II, III, and aVF. Transthoracic echocardiography revealed hypokinesis of the apex and interventricular septum and a hypoechoic mass in the LV (26 × 20 mm). She was diagnosed with acute arterial obstruction caused by the LV thrombus, which might have resulted from previous myocardial infarction. Protein C activation turned out to be low (41%) 5 days after admission. The anticoagulant therapy was switched from heparin to rivaroxaban 16 days after admission. The LV thrombus disappeared 24 days after initial treatment, and she has had no thrombotic episodes for 2.8 years under rivaroxaban therapy. Thrombophilia should be investigated for cases of simultaneous left ventricular and deep venous thrombi. Rivaroxaban can be effective in prevention of further thrombotic events.